Breakthrough innovations and productivity: An international perspective - Tero Kuusi; Jenni Nevavuo (The Research Institute of the Finnish Economy (ETLA), 2023)
In this paper, we shed new light on the productivity impact of breakthrough patents, as well as their role in the variability of productivity across countries. We use text analysis and machine learning-based estimates of the number of breakthrough patents and show that there was a significant drop in quantity in the early 2000s. According to our econometric analysis, the slowdown in innovation activity has a clear temporal connection with the later slowdown in productivity in the 2010s. Breakthrough patents increased productivity on a large scale until the beginning of the 2010s, in particular in industrial information and communications technology (ICT) industries. In sectors other than ICT, productivity growth was more differentiated so that productivity growth is observed in industries that invested significantly in R&D after the emergence of breakthrough patents. We also identify large differences across countries in the link between productivity and breakthrough patents.
Keywords: D24; O31; O33; 330; Productivity; Innovation; Breakthroughs; Patents